Inovasi Sosial Sebagai Strategi Program Pemberdayaan Kelompok Difabel Adaptif Kondisi Pandemi Melalui Program CSR PT PLN (Persero) Unit Induk Tanjung Jati B - Arifin, Miftah; Anam, A. Khoirul; Mahaputra, Wahyu (Universitas Islam Nahdlatul Ulama Jepara, 2021)
Empowerment is one of the strategies used in community development at this time. it can increase knowledge and power to reach a state of empowerment. Efforts to empower these vulnerable groups are carried out by PT PLN (Persero) Tanjung Jati B Generation Main Unit through a CSR program, namely the Sadifa Jepara Group. This empowerment program leads to strengthening the economy of the disabled community through various activities such as making herbal drinks, various types of soap, hand sanitizer, convection businesses, basic food businesses, and others. In addition, the activities carried out include training on strengthening MSMEs, providing equipment assistance, opportunities to develop networks by means of mass media publications as well as initiatives for sustainable and environmentally friendly economic activities. This service used 4-pillars model approach, namely the community as a supporting system and community activities, MSME Center, Communication and Cooperation Center, and the development of environmentally friendly products.